Ebola virus disease: An emerging and re-emerging viral threat (2020)
The genus Ebolavirus from the family Filoviridae is composed of five species including Sudan ebolavirus, Reston ebolavirus, Bundibugyo ebolavirus, Taï Forest ebolavirus, and Ebola virus (previously known as Zaire ebolavirus). These viruses have a large non-segmented, negative-strand RNA of approximately 19 kb that encodes for glycoproteins (i.e., GP, sGP, ssGP), nucleoproteins, virion proteins (i.e., VP 24, 30,40) and an RNA dependent RNA polymerase. These viruses have become a global health concern because of mortality, their rapid dissemination, new outbreaks in West-Africa, and the emergence of a new condition known as “Post-Ebola virus disease syndrome” that resembles inflammatory and autoimmune conditions such as rheumatoid arthritis, systemic lupus erythematosus and spondyloarthritis with uveitis. However, there are many gaps in the understanding of the mechanisms that may induce the development of such autoimmune-like syndromes. Some of these mechanisms may include a high formation of neutrophil extracellular traps, an uncontrolled “cytokine storm”, and the possible formation of auto-antibodies. The likely appearance of autoimmune phenomena in Ebola survivors suppose a new challenge in the management and control of this disease and opens a new field of research in a special subgroup of patients. Herein, the molecular biology, pathogenesis, clinical manifestations, and treatment of Ebola virus disease are reviewed and some strategies for control of disease are discussed. © 2019 The Authors